2017
DOI: 10.1186/s13223-017-0222-9
|View full text |Cite
|
Sign up to set email alerts
|

MPO-ANCA associated vasculitis with mononeuritis multiplex following influenza vaccination

Abstract: BackgroundAlthough influenza vaccines are generally safe and effective, a variety of autoimmune phenomena have been reported after vaccination over the past years, such as Guillain–Barre syndrome, rheumatoid arthritis, pemphigus vulgaris, psoriasis, giant cell arteritis and anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV).Case reportWe describe the case of a 67-year old man who presented with a myeloperoxidase-ANCA associated vasculitis with renal involvement and mononeuritis multiplex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Anti-Neutrophil Cytoplasmic Antibody (ANCA)- associated vasculitis (AAV) is a small vessel vasculitis hallmarked by the presence of antibodies against antigens in cytoplasmic granules of neutrophils. 6 While there are many case reports describing a temporal association between influenza vaccination and new onset/relapse of AAAV, 7 , 8 , 9 , 10 , 11 there are few reports of this occurring after receiving the COVID19 vaccine. 15 We report a case of new onset renal limited anti-myeloperoxidase (MPO)-AAV following COVID19 vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-Neutrophil Cytoplasmic Antibody (ANCA)- associated vasculitis (AAV) is a small vessel vasculitis hallmarked by the presence of antibodies against antigens in cytoplasmic granules of neutrophils. 6 While there are many case reports describing a temporal association between influenza vaccination and new onset/relapse of AAAV, 7 , 8 , 9 , 10 , 11 there are few reports of this occurring after receiving the COVID19 vaccine. 15 We report a case of new onset renal limited anti-myeloperoxidase (MPO)-AAV following COVID19 vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that vaccines contain adjuvant molecules that may provoke autoimmune responses. Additionally, vaccine antigens could trigger an autoimmune response via molecular mimicry [14][15][16][17]. Arguably, vaccine-associated AAV is more widely studied with the influenza vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated that influenza vaccination may trigger or exacerbate symptoms of a few autoimmune diseases such as Guillain–Barre syndrome, multiple sclerosis, and myeloperoxidase antineutrophil cytoplasmic antibody-associated vasculitis. [ 16 18 ] Although a causal link cannot be definitively established between influenza virus vaccination and the development of AIH, because immunization might be a possible cause of other autoimmune diseases, it is reasonable to hypothesize that influenza virus vaccination could trigger the development of AIH.…”
Section: Discussionmentioning
confidence: 99%